Development of Carbon Nanotube Supported Pt NPs for Oxygen Reduction of Fuel Cells - Kuang, Haohua (Curtin University, 2017)
The number of walls in pristine CNT supports has significant effects on the electrocatalytic activity of Pt nanoparticles towards ORR in both alkaline and acid conditions, with the electrocatalytic activity of Pt NPs showing distinctive volcano-type curves as a function of the number of walls. Double-walled CNTs (DWCNTs) composed of 2-3 walls exhibit better activity for ORR, compared with typical SWCNTs and MWCNTs. The findings explored a direction for developing high active and stable electrocatalysts.